Role of the SAFE pathway and the mitochondria in HDL cholesterol (and its constituent sphingosine-1-phosphate) induced cardioprotection - Hacking, Damian (Division of Cardiology, 2015)
High density lipoprotein cholesterol (HDL) and its component sphingosine-1-phosphate (S1P) protect against myocardial infarction. Recently, the SAFE (survivor activating factor enhancement) pathway, involving tumour necrosis factor (TNF) and the transcription factor signal transducer and activator of transcription 3 (STAT-3), has been identified as a key signalling pathway in cardioprotection, although the end effector remains unclear.